Mapping the Level of Lightning Strikes in Tabanan Regency - Ni Putu Winda Meidyani; Katarina Putu Dian Rusmala; Ni Wayan Mita Restitiasih; Ni Luh Putu Trisnawati (Jurnal Pendidikan Fisika, 2019)
This study aims to map the level of lightning strikes in Tabanan regency, Bali. Data collection was carried out in January to June 2016. There were ten subdistricts that became the location of the study, they are, Marga District, Kediri, Tabanan, Baturiti, Selemadeg, East Selemadeg, West Selemadeg, Pupuan, Penebel and Kerambitan. Mapping process in this study utilizes natural breaks classification and is processed using the 2000 lightning program and ArcGIS 9.3. The results obtained showed the map of lightning which is a map of lightning-prone areas in the area of Tabanan Regency. From these results, the regions most affected by lightning strikes are located in Pupuan and West Selemadeg Districts, while the areas with the least lightning strikes are located in clan districts. Furthermore, the results of this study can be used by the public and related to as a reference and information in minimizing the impact of lightning in everyday life.Keywords: Tabanan Regency, lightning, ArcGIS, lightning detector, natural breaksPenelitian ini bertujuan untuk mememetaan tingkat sambaran petir di kabupaten Tabanan, Bali. Pengambilan data dilakukan pada bulan Januari sampai Juni 2016. Terdapat sepuluh kecamatan yang menjadi lokasi penelitian antara lain, Kecamatan Marga, Kediri, Tabanan , Baturiti, Selemadeg, Selemadeg Timur, Selemadeg Barat, Pupuan, Penebel dan Kerambitan. Pemetaan dalam penelitian ini  menggunakan  klasifikasi  natural  breaks  dan  diolah  dengan  menggunakan  program lightning 2000 dan ArcGIS 9.3. Hasil yang diperoleh dari peta sambaran petir ini merupakan peta daerah rawan sambaran petir di wilayah Kabupaten Tabanan. Dari hasil tersebut, wilayah yang paling banyak terkena sambaran petir terletak pada Kecamatan Pupuan dan Selemadeg Barat, sedangkan daerah yang sedikit sambaran petir terletak pada kecamatan marga. Selanjutnya, hasil penelitian ini dapat digunakan oleh masyarakat dan pihat terkait sebagai acuan dan informasi dalam meminimalisir dampak petir dalam kehidupan sehari-hari.Kata kunci: Kabupaten Tabanan, petir, ArcGIS, lightning detector, natural breaks